Paternal care in the striped mouse Rhabdomys pumilio: ontogeny and function - Rymer, Tasmin Lee (My University, 2009)
Paternal care is rare and its development is poorly studied. I studied the ontogeny and function of paternal care in captive striped mice Rhabdomys pumilio from the succulent karoo, South Africa. Male striped mice show extensive parental care, displaying all behaviours (e.g. huddling and retrieving pups) shown by mothers, except nursing. In a first set of experiments, I studied non-genetic and genetic influences on the development of paternal care. The experimental design involved studying the development of paternal care in sons raised by the mother alone, both parents, and parents separated by a barrier. Sons raised by mothers alone were better fathers (i.e. displayed greater levels of paternal care behaviour) than sons from the other treatments; in contrast, daughters always showed higher levels of maternal care behaviour, regardless of treatment. Parent-offspring regressions indicated a partial patrilineal genetic influence of maternal (daughters), but not paternal (sons), care behaviour. Finally, sons raised by the mother and a second care-giver (older female sibling) also displayed better paternal care. My results indicate that fathers do not influence the development of paternal care in their sons genetically or nongenetically. Instead, an unanticipated finding was that mothers overcompensated in their maternal care behaviour in the absence of a male and the presence of a second care-giver, which correlated strongly with the greater levels of paternal care behaviour shown by their sons. In a second set of experiments, I investigated the role of the father in offspring learning, and female mate choice for males with different levels of paternal care behaviour. Using two populations of striped mice (succulent karoo and grassland), my results indicated that mothers were more reliable demonstrators of information about novel food in both populations, but fathers were more reliable demonstrators for young succulent karoo striped mice only. In mate choice tests for olfactory cues of males with different levels of paternal care ability and experience, and for visual cues from males showing either paternal or no care, females preferred experienced males to inexperienced males, but showed no other preferences. In conclusion, my results indicate that fathers are reliable demonstrators about novel food, at least in the succulent karoo, and supports previous findings that fathers are important for offspring development and survival in this population. However, the development of paternal care does not appear to be transmitted from fathers to sons (i.e. good fathers do not necessarily produce sons that are better fathers). This, together with the inability of females to distinguish between better and poor quality fathers, suggests that the level of paternal care is not as important as its mere occurrence, so that any paternal care would be beneficial to offspring.